Should one hire a corrupt CEO in a corrupt country? - Mironov, Maxim (Journal of Financial Economics, 2015)
This paper examines the interaction between the propensity to corrupt (PTC) and firm performance. Using a unique data set of Moscow traffic violations, I construct the PTC of every Muscovite with a driver׳s license. Next, I determine the PTC for the top management of 58,157 privately held firms. I find that a 1 standard deviation increase in management PTC corresponds to a 3.6% increase in income diversion and that firms with corrupt management significantly outperform their counterparts. This study contributes to the literature that characterizes corruption using objective (instead of perception-based) measures and provides evidence regarding the positive aspects of corruption at the firm level.